Geographical distribution, genetic studies and vector transmission of alfalfa enamovirus-1 infecting alfalfa crop in Argentina - Trucco, Verónica; Cabrera Mederos, Dariel; Lenardon, Sergio; Giolitti, Fabian (Virus genes, 2020)
Alfalfa ( Medicago sativa L.) growing areas of Argentina were surveyed between 2010 and 2018 to determine the geographical distribution and analyse the genetic diversity among alfalfa enamovirus-1 (AEV-1) isolates. The virus was detected in all 17 surveyed alfalfa-producing provinces, with a prevalence of 64%. The plant virus AEV-1 is widely distributed in the country, and its transmission vector has been unknown until now. Here we show that the black aphid Aphis craccivora can transmit AEV-1. The CP sequence identity among 16 AEV-1 isolates from Argentina was from 98 to 100% and from 98.9 to 100% at nucleotide and amino acid levels, respectively, indicating a low level of sequence variation among these isolates. The phylogenetic analysis based on the complete nucleotide sequence of the CP gene indicated that AEV-1 isolates are closely related and clustered in a monophyletic group. These results suggest that AEV-1 has spread very recently in Argentina. In the present study, we report the geographical distribution of AEV-1 in the main alfalfa-growing areas of Argentina and, for the first time, identify an insect vector and describe the CP gene diversity of an enamovirus worldwide.